C.S. Lewis's Christian apologetics : pro and con - Bassham, Gregory, 1959-; Baggett, David.; Barkman, Adam, 1979-; Johnson, David Kyle.; O'Hara, David, 1969-; Reppert, Victor, 1953-; Tallon, Philip.; Wielenberg, Erik J. 1972-; Williams, Donald T., 1951-; Williams, Peter S. (Value Inquiry Book Series, 2015)
Are C. S. Lewis's major arguments in defense of Christian belief sound? In C. S. Lewis's Christian Apologetics: Pro and Con , defenders and critics of Lewis's apologetics square off and debate the merits of Lewis's arguments from desire, from reason, from morality, the "trilemma" argument for the divinity of Christ, as well as Lewis's response to the problem of evil. By means of these lively, in-depth debates, readers will emerge with a deeper understanding and appreciation of today's most influential Christian apologist.